Gender, collective action, and climate change: Qualitative insights from Bangladesh, Ethiopia, Kenya, and Mali - Aberman, Noora-Lisa; Ali, Snigdha; Behrman, Julia A.; Bryan, Elizabeth; Davis, Peter; Donnelly, Aiveen; Gathaara, Violet; Koné, Daouda; Nganga, Teresiah; Ngugi, Jane; Okoba, Barrack; Roncoli, Carla (International Food Policy Research Institute, 2014)
Climate change poses great challenges for poor rural people in developing countries, most of whom rely on natural resources for their livelihoods and have limited capacity to adapt to climate change. It has become clear that even serious efforts to mitigate climate change will be inadequate to prevent devastating impacts that threaten to erode or reverse recent economic gains in the developing world. Individuals, communities, and policymakers must adapt to a new reality and become resilient to the negative impacts of future climate changes. Research has demonstrated that assets, broadly defined to include natural, physical, financial, human, social, and political capital, play a fundamental role in increasing incomes, reducing vulnerability, and providing pathways out of poverty. Assets are essential to poor peoples’ ability to cope with climatic shocks and to adapt to the long-term impacts of climate change.